Development and validation of service quality scale for Indian telecom sector. (9th December 2020) - Agariya, Arun Kumar; Tikoria, Jyoti
Looking at the changing landscape of Indian telecom sector due to the fierce competition and price war, there is need to reconsider and prioritise the current service standards to measure service quality. The research work aims at developing a valid and reliable scale for assessing the service quality of telecom service providers in India. A standard methodology for scale development is used for developing and validating the scale, which comprises of exploratory and confirmatory factor analysis. The sample population was taken from National Capital Region (NCR) of India. The findings clearly reveal the service quality as a multidimensional construct comprising of the factors namely physical infrastructure, service encounter, employee conduct, customer support and agility. The study bridges the gap in the literature in the domain of service quality as well as provides inferences and strategic implications from practitioner's perspective as well. Novelty of this work lies in the fact of considering the views of customers of different Indian telecom service providers and providing a comprehensive measure for enhancing the service quality which is the pressing need due to the significant change in the Indian telecom sector due to advent of new players as well as shifting customer expectations and experiences.